PERKEMBANGAN AFEKTIF SISWA SDN 03 MANGLIAWAN MALANG DI ERA DISRUPSI MASA PANDEMI - Muchamad Khilmi; Devi Wahyu Ertanti; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
The theme that the researchers took was about the researchers' interest in students' affectiveness. After that the researcher conducted a study entitled